Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2011)
Significant progress has been made towards meeting the fund-raising targets for the PRGT, but additional resources will be needed to complete the 2009 LIC financing package. So far, fourteen members have pledged about SDR 9.8 billion in new loan resources, compared to the target of SDR 10.8 billion (including provision for a liquidity buffer to facilitate encashment). New borrowing agreements totaling SDR 7.7 billion have been signed with ten lenders. Six of these agreements provide loan resources in SDRs, and five creditors also participated in the voluntary encashment regime.